Trauma-focused psychodynamic therapy and STAIR Narrative Therapy of post-traumatic stress disorder related to childhood maltreatment: trial protocol of a multicentre randomised controlled trial assessing psychological, neurobiological and health economic outcomes (ENHANCE). Issue 12 (17th December 2020) - Leichsenring, Falk; Steinert, Christiane; Beutel, Manfred E.; Feix, Lila; Gündel, Harald; Hermann, Andrea; Karabatsiakis, Alexander; Knaevelsrud, Christine; König, Hans-Helmut; Kolassa, Iris T.; Kruse, Johannes; Niemeyer, Helen; et al.
Abstract : Introduction: Success rates of psychotherapy in post-traumatic stress disorder related to childhood maltreatment (PTSD-CM) are limited. Methods and analysis: Observer-blind multicentre randomised clinical trial (A-1) of 4-year duration comparing enhanced methods of STAIR Narrative Therapy (SNT) and of trauma-focused psychodynamic therapy (TF-PDT) each of up to 24 sessions with each other and a minimal attention waiting list in PTSD-CM. Primary outcome is severity of PTSD (Clinician-Administered PTSD Scale for DSM-5 total) assessed by masked raters. For SNT and TF-PDT, both superiority and non-inferiority will be tested. Intention-to-treat analysis (primary) and per-protocol analysis (secondary). Assessments at baseline, after 10 sessions, post-therapy/waiting period and at 6 and 12 months of follow-up. Adult patients of all sexes between 18 and 65 years with PTSD-CM will be included. Continuing stable medication is permitted. To be excluded: psychotic disorders, risk of suicide, ongoing abuse, acute substance related disorder, borderline personality disorder, dissociative identity disorder, organic mental disorder, severe medical conditions and concurrent psychotherapy. To be assessed for eligibility: n=600 patients, to be e randomly allocated to the study conditions: n=328. Data management, randomisation and monitoring will be performed by an independent European Clinical Research Infrastructure Network (ECRIN)-certified data coordinating centre for clinical trials (KKS Marburg). Report of AEs to a data monitoring and safety board. Complementing study A-1, four inter-related add-on projects, including subsamples of the treatment study A-1, will examine (1) treatment integrity (adherence and competence) and moderators and mediators of outcome (B-1); (2) biological parameters (B-2, eg, DNA damage, reactive oxygen species and telomere shortening); (3) structural and functional neural changes by neuroimaging (B-3) and (4) cost-effectiveness of the treatments (B-4, costs and utilities). Ethics and dissemination: Approval by the institutional review board of the University of Giessen (AZ 168/19). Following the Consolidated Standards of Reporting Trials statement for non-pharmacological trials, results will be reported in peer-reviewed scientific journals and disseminated to patient organisations and media. Trial registration number: DRKS 00021142.